2020
DOI: 10.3390/jcm9103253
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Related Diseases and Osteoporotic Fractures (Narrative Review)

Abstract: Osteoporosis (OP) and osteoporotic fractures (OFs) are common multifactorial and heterogenic disorders of increasing incidence. Helicobacter pylori (H.p.) colonizes the stomach approximately in half of the world’s population, causes gastroduodenal diseases and is prevalent in numerous extra-digestive diseases known to be associated with OP/OF. The studies regarding relationship between H.p. infection (HPI) and OP/OFs are inconsistent. The current review summarizes the relevant literature on the potential role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 748 publications
(832 reference statements)
1
14
0
Order By: Relevance
“…This should also explain the association between peptic ulcer disease and osteoporosis reported by several studies [ 149 , 150 , 151 ]. In fact, HP is responsible for 85% of gastric ulcers and 95% of duodenal ulcers [ 152 ]. In particular, an increased risk of osteoporosis was described in two large studies from Korea (with HR ranging from 1.36 to 1.72) [ 149 , 150 ], as well as in a population-based study from Taiwan (HR = 1.85, 95% CIs = 1.73–1.98) [ 153 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
“…This should also explain the association between peptic ulcer disease and osteoporosis reported by several studies [ 149 , 150 , 151 ]. In fact, HP is responsible for 85% of gastric ulcers and 95% of duodenal ulcers [ 152 ]. In particular, an increased risk of osteoporosis was described in two large studies from Korea (with HR ranging from 1.36 to 1.72) [ 149 , 150 ], as well as in a population-based study from Taiwan (HR = 1.85, 95% CIs = 1.73–1.98) [ 153 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
“…From a histopathological aspect, CAG leads to a reduction in the intrinsic glands of the gastric mucosa and even fibrous replacement, intestinal epithelial metaplasia, and even atypical hyperplasia due to long-term damage to the gastric mucosa ( Li et al, 2018 ). In addition to being a risk factor for gastric cancer, CAG is also clinically related to various disorders, including intestinal metaplasia and dysplasia ( Li et al, 2018 ), depression ( Zhao et al, 2018 ), and damaged skeletal health ( Fisher et al, 2020 ). The current treatment for CAG focuses on symptomatic treatment such as triple therapy ( Tarasconi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms of diffusions are gastric reflux and nasal or oral routes, where laryngopharyngeal reflux may contribute to many sinonasal, laryngeal, pharyngeal, and middle ear disorders; however, there is no clear evidence of the active role of H. pylori in otorhinolaryngological diseases [ 5 ]. H. pylori infection has also been linked with some extra-digestive diseases i.e., iron deficiency anemia [ 6 ], idiopathic thrombocytopenic purpura [ 7 , 8 ], hepatobiliary diseases [ 9 , 10 ], nonalcoholic fatty liver disease [ 11 ], diabetes mellitus [ 12 , 13 ], cardiovascular disorders [ 14 , 15 ], neurodegeneration (Alzheimer’s disease, Parkinson’s disease, and glaucoma) [ 16 , 17 , 18 ], and osteoporosis [ 19 , 20 , 21 ]. Osteoporosis, with the burden of bone fragility and osteoporotic fractures it brings, is a common multifactorial disorder of increasing incidence.…”
Section: Introductionmentioning
confidence: 99%
“…A large meta-analysis demonstrated that patients with H. pylori infection are at a high risk of developing osteoporosis [ 21 ]. Interestingly, recent data suggests that osteoporosis and many of the extra-digestive diseases associated with H. pylori infection share risk factors and pathogenetic pathways [ 19 ]. In this connection, it can be noted that diabetes mellitus, a prominent extra-digestive disease associated to H. pylori infection, adversely impacts on skeleton and bone health, and is associated with an increased risk of osteoporosis and fragility fractures [ 22 ].…”
Section: Introductionmentioning
confidence: 99%